Knowledge, attitude, practice and awareness of students on breast self-examination: a cross-sectional study - Akinola, Ajoke; Mukaddas, Zulaiha Muhammad (International Journal Of Community Medicine And Public Health, 2021)
Background: Breast cancer is the leading cause of cancer related deaths globally. it is the common malignancy in women. Lack of early detection leads to low survival rates. Breast self-examination (BSE) is a screening technique that involves examining the breasts for lumps. The aim of the study was to assess the knowledge, attitude and practice of breast self-examination, among the students. Methods: A cross sectional study was carried out in Noida International University, Greater Noida, Uttar Pradesh, India. Quantitative data was collected using a structured questionnaire, filled by 100 female university students that were selected by convenient sampling method. Descriptive analysis of data was done using SPSS version 17.0 (Chicago USA). Results: Out of the 100 participants 83% were in the age group of 15-25 years, 25% of them had family history of breast cancer, and it was revealed that majority of them (94%) have heard of breast cancer and 85% of them heard of breast examination. Despite the high knowledge that was cited among the participants, only 43% of them were having good attitudes towards BSE and only 51% among them have ever practiced BSE. Conclusions: The study revealed good knowledge, negative attitude and low practice towards BSE among the students of Noida International University, Greater Noida, UP State, India. Therefore, there is need to plan and prepare materials for educating the students on BSE to improve primary prevention of breast cancer.